People we meet on vacation - Henry, Emily (New York : Jove, 2021)
"When Poppy met Alex, there was no spark, no chemistry, and no reason to think they'd ever talk again. Alex is quiet, studious, and destined for a future in academia. Poppy is a wild child who only came to U of Chicago to escape small-town life. But after sharing a ride home for the summer, the two form a surprising friendship. After all, who better to confide in than someone you could never, ever date? Over the years, Alex and Poppy's lives take them in different directions, but every summer the two find their way back to each other for a magical week long vacation. Until one trip goes awry, and in the fallout, they lose touch. Now, two years later, Poppy's in a rut. Her dream job, her relationships, her life - none of it is making her happy. In fact, the last time she remembers feeling truly happy was on that final, ill-fated Summer Trip. The answer to all her problems is obvious: She needs one last vacation to win back her best friend. As a hilariously disastrous week unfolds and tensions rise, Poppy and Alex are forced to confront what drove them apart - and decide what they're willing to risk for the chance to be together."--
"A Jove Book"--Title page verso.
Includes reader's guide.
108945
Keywords: Travel writers -- Fiction; Man-woman relationships -- Fiction; Best friends -- Fiction; Vacations; Reconciliation; Self-realization; Fiction; Romance fiction; Love stories; Humorous fiction